PERTUMBUHAN GEREJA YANG DINAMIS BERDASARKAN KAJIAN BIBLIKA - Johanes Witoro (STT BIBLIKA JAKARTA, 2023)
During the Covid-19 period, the pattern of church worship changed from onsite to online. Even though the church is currently able to carry out onsite worship, there are still many congregations who are preoccupied with online and do not attend onsite worship. Many churches have remained stagnant, not experiencing growth after the Covid 19 pandemic, so the purpose of this research is to see the existence of the church today, to see how far the church has experienced growth. The Bible provides many principles of coaching with the aim that many servants of God and pastors want to learn the basic principles of dynamic church growth. This study uses qualitative research using interpretations of Bible texts to obtain the main principles. The result of this research is that the pastor needs to be a figure who plays a major role, as a role model, who pays attention to the congregation, someone who is consistent in his ministry, and several other important attitudes.